Analisis Hubungan Kinerja Ruas Jalan terhadap Emisi Gas Buang Karbon Monoksida (CO) pada Jalan Nasional Lingkar Timur I Kota Jambi - Soni Ade Sudirjo; Rinaldi Rinaldi; Ade Nurdin (Jurnal Talenta Sipil, 2023)
Jambi City moves quickly in all fields including one of its transportation activities. The negative impact of transportation activities is the exhaust emissions emitted by vehicle smoke which are toxic to the surrounding air. Air pollution that has an impact on transportation activities reaches more than 50%. The East Ring Road Section I of Jambi City is one of the national roads, where this road has a relatively high traffic volume, and when viewed visually this road is one of the roads that contribute to the large level of vehicle exhaust emissions. One of the things that trigger vehicles to become more congested due to the presence of several activity centers. The purpose of this study is to determine the relationship between carbon monoxide (CO) exhaust emissions and traffic volume and degree of saturation. The method used in this study is a quantitative descriptive method. The data collection techniques used are surveys and observations. From the results of the study, it was obtained that the road capacity was 2914 smp/hour with the traffic flow on the road section exceeding the road capacity and the average DS value of 0.96 exceeding the standard based on the 1997 MKJI of 0.75. This shows that the congested road capacity cannot accommodate the traffic flow that occurs and the flow of vehicles moves with many obstacles. Based on the analysis with the correlation method and regression method between the degree of saturation and carbon monoxide gas, it was found that the degree of saturation and carbon monoxide gas has a strong relationship with the positive correlation result, meaning that if the degree of saturation increases, there will also be an increase in carbon monoxide gas.